2021
DOI: 10.1002/ncp.10742
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations of developing and conducting a successful telehealth practice in response to COVID‐19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic posed significant challenges to clinicians practicing in outpatient settings focused on chronic disease treatment and management. Many interprofessional teams transitioned to telehealth to continue to provide care while minimizing in-person interaction to reduce risk of transmission. Given that telehealth will likely remain as a care option even as the pandemic subsides, this review summarizes the applied recommendations on telehealth in interprofessional patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…With the onset of COVID-19, there have been striking changes in health care, which likely has affected perceived benefits and challenges of telehealth utilization in rural communities. Telehealth utilization was historically low and limited in scope and range prior to the pandemic (Guitton, 2021), often attributable to logistical and financial limitations, limited access and skills related to technology, and low rates of reimbursement coverage for both patients and providers (Tewksbury et al, 2021). A Duke University study examined statistics from U.S. healthcare organizations, including its own (Wosik et al, 2020).…”
Section: Telehealth and The Covid-19 Pandemicmentioning
confidence: 99%
“…With the onset of COVID-19, there have been striking changes in health care, which likely has affected perceived benefits and challenges of telehealth utilization in rural communities. Telehealth utilization was historically low and limited in scope and range prior to the pandemic (Guitton, 2021), often attributable to logistical and financial limitations, limited access and skills related to technology, and low rates of reimbursement coverage for both patients and providers (Tewksbury et al, 2021). A Duke University study examined statistics from U.S. healthcare organizations, including its own (Wosik et al, 2020).…”
Section: Telehealth and The Covid-19 Pandemicmentioning
confidence: 99%
“…Remote assessments and interventions have been previously proposed as a mechanism to deliver these interventions [ 33 ]. However, with the effects of COVID-19, many bariatric programs have been able to overcome many of the barriers to implementing this care and, in turn, expand access for patients without compromising quality [ 34 , 35 ]. Based on retrospective analysis, bariatric clinicians have suggested that in-person sessions are not necessary to screen for potential postoperative issues.…”
Section: Intervention Settingsmentioning
confidence: 99%
“…[55,56]. This shift to responsibility, cost-proficiency, populace wellbeing, and care experience is driving the fast reception of telehealth across the medical care industry [57][58][59][60]. The development of virtual medical services isn't just expanding doctor access and driving down costs, but on the other hand is setting out open doors for innovation organizations to give quicker, more helpful patient encounters -bringing about further developed results and an upgraded experience [61][62][63].…”
Section: The Possible Nexus Of Sustainable Development Health and Tec...mentioning
confidence: 99%